IMPLEMENTASI TATA LAKSANA BUDAYA KESELAMATAN PASIEN DALAM PELAYANAN KESEHATAN DI PUSKESMAS MEREK KABUPATEN KARO - Febi Sany Venensia Lumbantobing; Muhammad Husni Thamrin (CV. Denasya Smart Publisher, 2025)
Improving the quality of healthcare services requires the implementation of a patient safety culture as the primary pillar for consistently integrating safety principles policies and procedures. This research is carried out to examine the implementation of patient safety culture management at the Merek Community Health Center, Karo Regency, which still faces various obstacles such as a lack of guidelines, limited resources, and insufficient training. This research used a descriptive qualitative approach through interviews, observations and documentation, and analysis referring to George C. Edwards III's policy implementation theory and the dimensions of patient safety culture. The findings point to the conclusion that implementation has not been carried out comprehensively, especially in aspects of communication, understanding of health workers, and reporting and learning culture. Continuous training, a more flexible reporting system, and institutional support are needed to strengthen the holistic application of patient safety values and practices.